CLINICAL AND MICROBIOLOGICAL PROFILE OF SECONDARY BLOODSTREAM INFECTIONS RESULTING FROM URINARY TRACT INFECTION CAUSED BY ENTEROBACTERALES - NANDHINI S; ARUNAVA KALI; VALENTINA Y; PRAVIN CHARLES M.V; JOSHY M EASOW (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Bloodstream infection (BSI) is a common sequelae of urinary tract infections (UTIs) and it requires early detection and appropriate antibiotic therapy. This study analyzed the clinical and microbiological profile of secondary BSI resulting from UTI caused by Enterobacterales. Methods: In this retrospective study, National Healthcare Safety Network criteria were used to define the cases of UTI and secondary BSI attributed to UTI. Data from medical records and laboratory reports of patients from January to May 2024 were compiled and analyzed. Results: Among 932 urine samples with significant growth of Enterobacterales, 48 were blood cultures positive. Out of them, 26 patients (11 males and 15 females) met the criteria of BSI secondary to UTI as the same isolates also grew in blood specimens which was taken within the secondary BSI attribution period. Nine patients had catheter-associated symptomatic UTI (CA-SUTI) while 14 were non-CA-SUTI and 3 had asymptomatic bacteriuria. In urine culture, Escherichia coli (n=22, 68.1% multi-drug resistant and 31.8% non-multi-drug resistant [MDR]), Klebsiella pneumoniae (n=3, all MDR), and Citrobacter koseri (n=1, non-MDR) strains were isolated. Diabetes, renal calculi, fever, Foley’s catheter, age >60 years, intensive care unit admission, and hospital stay >10 days were more among individuals with MDR infections. Cefoperazone-sulbactam, piperacillin/tazobactam, and nitrofurantoin had good outcomes. Conclusion: Cefoperazone-sulbactam, piperacillin/tazobactam, and nitrofurantoin were effective for treating patients with BSI attributed to UTI in our hospital with good outcomes. Hence, these antibiotics might have a critical role as empirical therapy for such, particularly those with underlying health conditions and risk factors for MDR infections.